In Vivo Antihypertensive And In Vitro Vasodilatory Studies Of Reformulated Banxia Baizhu Tianma Tang: Pharmacological Optimisation Using Orthogonal Stimulus-Response Compatibility Model - Tan, Chu Shan (2017)
Banxia Tianma Baizhu Tang (BBT) is one of the most common Traditional Chinese Medicine (TCM) used for treating hypertension. However, differences in the herbs’ geographical location, time of harvest and processing when compared to ancient times has warranted modification in the formula. Although modification of BBT have been previously done (by addition of one or two other herbs in BBT), optimal reformulation of BBT for anti-hypertension has not been carried out. The authenticities of six raw herbs of BBT were verified by high performance thin layer chromatography (HPTLC) and Fourier transform infrared (FTIR) fingerprints identification methods. Three solvents (95%, 50% ethanol and water) were used for maceration process. The vasodilatory effects of all extracts were investigated by using the in vitro isolated aortic rings assays. Among the extracts, water extract of P. ternata [PT(W)] and C. reticulatae [CR(W)], 50% ethanol extract of G. elata [GE(50)] and G. uralensis [GU(50)], and 95% ethanol extract of A. macrocephala [AM(95)] and P. cocos [PC(95)] were found as the most potent extracts for exerting vasodilatory effects.